Preoperative AT-III Values and Clinical Postoperative Thrombosis: A Comparison of Three Antithrombin-III Assays - Lynch, Dona M; Leff, Linda K; Howe, Stephen E (Thrombosis and Haemostasis, 1984)
Three antithrombin-III assays (Sigma functional plasma, von Kaulla functional serum, and Calbiochem-Behring radial immunodiffusion) are compared using preoperative serum and plasma from 48 patients admitted for cardiovascular or other major vascular surgery. Medical records were reviewed for evidence of thrombotic complications. Eight patients (17%) in this selected population had clinical evidence of postoperative thrombotic complications. The sensitivity and specificity for each AT-III assay were calculated, and the positive and negative predictive values in this population were determined. Sigma’s plasma AT-III had the highest positive predictive value (67%) and negative predictive value (100%). The functional serum and RID assays had significantly lower positive predictive values (23% and 38% respectively) and negative predictive values of 86%. Using the Two Sample t-Test to evaluate differences in AT- III values between the two patient groups, i.e., those who experienced thrombotic complications and those who did not, only the functional plasma AT-III method was statistically significant at a 95% confidence interval.
Keywords: Antithrombin-III; Thrombosis; Cardiovascular surgery